Sugar signals pedal the cell cycle! - Rawat, Sanjay Singh; Laxmi, Ashverya (Frontiers in Plant Science, 2024)
Cell cycle involves the sequential and reiterative progression of important events leading to cell division. Progression through a specific phase of the cell cycle is under the control of various factors. Since the cell cycle in multicellular eukaryotes responds to multiple extracellular mitogenic cues, its study in higher forms of life becomes all the more important. One such factor regulating cell cycle progression in plants is sugar signalling. Because the growth of organs depends on both cell growth and proliferation, sugars sensing and signalling are key control points linking sugar perception to regulation of downstream factors which facilitate these key developmental transitions. However, the basis of cell cycle control via sugars is intricate and demands exploration. This review deals with the information on sugar and TOR-SnRK1 signalling and how they manoeuvre various events of the cell cycle to ensure proper growth and development.